ANALISIS PENGARUH CELEBRITY ENDORSER DAN KEINOVATIFAN PRODUK TERHADAP KEPUTUSAN PEMBELIAN, SERTA CITRA MEREK DAN NILAI UTILITARIAN SEBAGAI VARIABEL INTERVENING. (STUDI PADA PENGGUNA PROVIDER SELULER XL DI SEMARANG) - Shafira, Anastania; Ferdinand, Augusty Tae (Diponegoro Journal of Management, 2017)
This study aims to explain the influence of celebrity endorser and product innovativeness in order to influence purchasing decision, which brand image and utilitarian value are used as intervening variables between celebrity endorser and product innovativeness to purchasing decision XL provider in Semarang. This research was conducted by taking samples using purposive sampling technique. The collection of data obtained from 100 XL users in SemarangÂ  by giving questionnaires which consist of open and closed questions. The analysis technique used in this research is Multiple Linier Regression of SPSS 23 program. The first regression to analyze the effect of celebrity endorser on brand image. The second regression to analyze the effect of product innovativeness to utilitarian value, while the third regression to analyze effect of brand image and utilitarian vaue on purchase decision. The result show that celebrity endorser has positive and significant impact on brand image. Product innovativeness has positive and significant impact on utilitarian value. Brand image and utilitarian value also have positive and significant impact on purchasing decision.